Alcohol use in emerging adults associated with lower rich-club connectivity and greater connectome network disorganization. (1st January 2022) - Hua, Jessica P.Y.; de Lange, Siemon C.; van den Heuvel, Martijn P.; Boness, Cassandra L.; Trela, Constantine J.; McDowell, Yoanna E.; Merrill, Anne M.; Piasecki, Thomas M.; Sher, Kenneth J.; Kerns, John G.
Abstract: Background: Emerging adulthood is a critical neurodevelopmental stage, with alcohol use during this period consistently associated with brain abnormalities and damage in anatomical structure and white matter integrity. However, it is less clear how alcohol use is associated with the brain's structural organization (i.e., white matter connections between anatomical regions). Recent connectome research has focused on rich-club regions, a collection of highly-interconnected hubs that are critical in brain communication and global network organization and disproportionately vulnerable to insults. Methods: For the first time, we examined alcohol use associations with structural rich-club and connectome organization in emerging adults ( N  = 66). Results: Greater lifetime drinks and current monthly drinks were significantly associated with lower rich-club organization ( r s =−0.38, p s < 0.003) and lower rich-club connectivity ( r s <−0.34, p s < 0.007). Additionally, rich-club connectivity was significantly more negatively correlated with alcohol use than connectivity among non-rich-club regions ( p s < 0.035). Examining overall structural organization, greater lifetime drinks and current monthly drinks were significantly associated with lower network density (i.e., lower network resilience; r s <−0.36, p s = 0.004). Additionally, greater lifetime drinks and current monthly drinks were significantly associated with higher network segregation (i.e., network's tendency to divide into subnetworks; r s >0.33, ps <0.008). Alcohol use was not significantly associated with network integration (i.e., network's efficiency in combining information across the brain; p s > 0.064). Conclusions: Results provide novel evidence that alcohol use is associated with decreased rich-club connectivity and structural network disorganization. Given that both are critical in global brain communication, these results highlight the importance of examining alcohol use and brain relationships in emerging adulthood. Highlights: Young adulthood is a critical neurodevelopmental stage with high rates of drinking. Examined alcohol use associations with connectome organization in emerging adults. Specifically examined rich-club connectivity and structural network organization. Greater alcohol use was associated with decreased rich-club connectivity. Greater alcohol use was associated with greater structural network segregation.